2022
DOI: 10.3390/nano12071204
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Analysis of Nanostructured Material Flow over an Exponentially Stretching Surface: A Comparative Study

Abstract: The objective of the present research is to obtain enhanced heat and reduce skin friction rates. Different nanofluids are employed over an exponentially stretching surface to analyze the heat transfer coefficients. The mathematical model for the problem has been derived with the help of the Rivilin–Erickson tensor and an appropriate boundary layer approximation theory. The current problem has been tackled with the help of the boundary value problem algorithm in Matlab. The convergence criterion, or tolerance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Sreedevi et al 31 revealed that when carbon nanotubes and silver nanoparticles combine and are taken as hybrid nanoparticles then water is viewed as base fluid. Mubashar et al 32 investigated about the three—DGO nanoliquid flow over the exponentially elastic surface. They considered water is used as a base fluid whilst three exceptional nanoparticles, specifically zinc, copper, and silver are viewed for this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Sreedevi et al 31 revealed that when carbon nanotubes and silver nanoparticles combine and are taken as hybrid nanoparticles then water is viewed as base fluid. Mubashar et al 32 investigated about the three—DGO nanoliquid flow over the exponentially elastic surface. They considered water is used as a base fluid whilst three exceptional nanoparticles, specifically zinc, copper, and silver are viewed for this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Gowda et al [14] have demonstrated Casson-Maxwell fluid through stretchable disks to examine slip flow [15][16][17][18][19]. and Arshad et al [20][21][22] have extensively examined linear and exponential stretching surfaces with external applied effects for nano and hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Hassan et al [ 12 ] elaborated a prescribed wall temperature case with magneto-hydrodynamic radiative hybrid particles. Arshad et al [ 13 ] examined the comparative analysis of heat transfer of a nanostructured material over an exponentially stretching sheet. Arshad et al [ 14 ] interpreted the Brownian and thermophoresis diffusion of a chemically reacting magneto-hydrodynamic nanofluid over an exponentially stretching sheet.…”
Section: Introductionmentioning
confidence: 99%